The Psychological Aspect of Integrated Art Education - Matijkienė, Dalia (Acta Paedagogica Vilnensia, 2002)
The article deals with psychological aspects of fine arts curriculum for teenagers. The modem trends of global cultural development, including Lithuania, which express themselves in post-modernist ideas of pluralism, polarity and axiological indifference, are decisive in arts education. They reveal a main problem of the elements ratio in the content of education: the problem of relationship between theoretical knowledge and practical creative activity. In psychological aspect, this problem evokes the question of linkage between fundamental opposing human substances of emotions and intellect, rational and irrational, in the development of a congruous and consistent person. This problem can be solved on the basis of psychological theories of L. Vygotskij, R. Amheim and W. Dilthey; they prove a synthetic nature of art and creativity as well as the complex and multifaceted nature of art and artistry perception that draw together all the essential qualities of a human being including spheres of emotions, intuition and abstract thought. Decisive role in construction of art education system should be assigned to intuition: that will help us to find an optimal ratio of rational and irrational elements that evokes artistic intuition and creativity. In opinion of the teachers working with 12-16 year old teenagers the perception of artistic artefact as well as the process of its creation should be based on matching of practical activities and theoretical knowledge. This proves that while devising a system of artistic education for students of this age a very important role should be attached to the practical creative expression, at the same time linking it with the comprehension of the world culture (it is a task of methodology to find a balanced proportion of the two main elements). The perception of art objects should be based on their direct observation, analysis and theoretical knowledge, and on the basic knowledge of composition. All these components must be harmonized. At the same time all these components must be rooted in personai experience and theoretical knowledge.